Penerapan SAK EMKM dalam Menyusun Laporan Keuangan UMKM pada Seblak Prasmanan Bunda Kota Pekanbaru - Nurlita, Amelia; Rodiah, Siti; Ramadhani, Andini; Hayati, Syarifatul; Sarmila, Wingki (International Forum of Researchers and Lecturers, 2024)
A standard known as SAK EMKM regulates MSMEs (Micro, Small and Medium Enterprises).finances. This research aims to apply SAK EMKM as a basis for preparing financial reports for Seblak Prasmanan Bunda MSMEs, which are MSMEs that have developed and should have prepared their financial reports based on SAK EMKM. However, in preparing it, they experienced difficulties or obstacles in preparing financial reports based on SAK EMKM. This research aims to find out and examine what obstacles MSMEs face in preparing simple financial reports based on SAK EMKM. This research uses a qualitative approach using the case study method. The data sources used are primary data and secondary data. The results of the research show that in preparing financial reports, MSME actors have not implemented SAK EMKM due to business actors never receiving socialization, minimal educational background of MSME actors, no regulations related to the implementation of SAK EMKM, low capital to employ expert staff in preparing financial reports and business facilities. Therefore, in this research, a simple financial report was created which can help MSMEs understand how to prepare financial reports based on SAK EMKM.